If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + -5) = 5(y + -5) Reorder the terms: 6(-5 + y) = 5(y + -5) (-5 * 6 + y * 6) = 5(y + -5) (-30 + 6y) = 5(y + -5) Reorder the terms: -30 + 6y = 5(-5 + y) -30 + 6y = (-5 * 5 + y * 5) -30 + 6y = (-25 + 5y) Solving -30 + 6y = -25 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -30 + 6y + -5y = -25 + 5y + -5y Combine like terms: 6y + -5y = 1y -30 + 1y = -25 + 5y + -5y Combine like terms: 5y + -5y = 0 -30 + 1y = -25 + 0 -30 + 1y = -25 Add '30' to each side of the equation. -30 + 30 + 1y = -25 + 30 Combine like terms: -30 + 30 = 0 0 + 1y = -25 + 30 1y = -25 + 30 Combine like terms: -25 + 30 = 5 1y = 5 Divide each side by '1'. y = 5 Simplifying y = 5
| 11=2x-5 | | 7x-8=6x+2 | | 9x+26=5x | | 3-x/4=2 | | 2x^3+5x^2=6x+9 | | 5x+11=4x+16 | | 8x-0.4=9x | | 4(3y-6)=36 | | 6w^2-7w^3=0 | | 16a=3(2a+10) | | 16a=3(2+10) | | 3(v-8)=9v-12 | | 5x-9=8x-4x | | 4x-(2x-6)=90 | | t(x)=x^2+9x+20 | | 13x+12=14x+5 | | 5x-9=9x-4x | | -5x+3=-(x-33) | | 0.05z+0.2=0.15z+10.5 | | 15x-20x^2=0 | | -54=6n | | 7x^2-6x+5=0 | | 3+3u=-15 | | 2w^2-3w-65=0 | | x/4=-20+16 | | 4.5x+2x-9=17 | | 13-7x=168-42x | | 18-3(2.5)= | | 7x-5=21 | | 2c+6=6c-4 | | 20y^2-13y+2=0 | | 2=-1+-x |